Ramalan (ke)Nabi(an) Terbayangkan untuk Indonesia Masa Kini - Susanto, Budi (Jurnal Orientasi Baru, 2013)
Prophecy used to be understood as something of the future or of the past, whether it is about something good or not good. On the other hand, prophecy is often explained as a coming event or a prediction of something that might happen. That explanation could be considered as of mystical aspect of a prophecy, or something about a â€œfuture of tomorrowâ€. In our modern or postmodern era, our question is what could be the role of mass-media in relation to that prophecy and the prophet of today? Indeed, todayâ€™s prophet could make use of mass-media, printed or virtually printed, to publish or distribute his or her message. Presumably, this kind of prophecy would generate similar social-religious movement and action that eventually would have impact on the social-political and cultural life of a society and nation.